Antioxidant and Chemosensitizing Effects of Flavonoids with Hydroxy and/or Methoxy Groups and Structure-Activity Relationship - Ju-Mi Jeong; Cheol-Hee Choi; Su-Kyeong Kang; In-Hwa Lee; Ji-Yoon Lee; Hyuk Jung (Frontiers Media S.A., 2007)
Purpose. Flavonoids have been used as antioxidant, chemopreventive and chemosensitizing agents. In this study, eleven flavonoids containing a variety of hydroxy (OH) and/or methoxy (OMe) groups were evaluated for their antioxidant, cytotoxic and chemosensitizing effects to create a structure-activity relationship (SAR). Methods. 1,1-Diphenyl-2-picrylhydrazyl (DPPH) radical solution-based chemical assay and and 2',7'-dichlorofluorescin diacetate (DCFH-DA) cellular-based assay were used to compare the free radical scavenging activity on the same molar concentration basis using the AML-2/DX100 cells which are characterized by the down-regulated expression of catalase and resulting supersensitiviy to hydrogen peroxide. The chemosensitization and cytotoxicity were determined by the MTT assay in the presence or absence of an anticancer drug using the P-glycoprotein-overexpressing AML-2 subline AML-2/D100 cells. Results. The antioxidant activity of the flavonoid (3,5,7,3',4'-OH) was higher than that of the flavonoid (5,7,3',4'-OH). Flavonoids substituted with the various number of OMe decreased antioxidant activity. Flavonoids with 7-OH or 5,7-OH groups have the highest cytotoxicity, and flavonoids with 5,7-OMe group intermediate cytotoxicity. The IC50 values of flavonoid (5,7-OMe, 3',4',5'-OMe) and flavonoid (5,7-OMe, 4'-OMe), 0.4 M and 1.4 M. The IC50 values of flavonoid (5,6,7-OMe, 3',4'-OMe) and flavonoid (5,6,7-OMe, 3',4',5'-OMe), 3.2 uM and 0.9 M, respectively, and those of flavonoid (5,6,7-OMe, 3',4',5'-OMe) and flavonoid (5,7-OMe,3',4',5'-OMe) were 0.9 M and 0.4 M, respectively. Conclusions. These results suggest that flavonoids with 3-OH group play a positive role in antioxidant activities, flavonoids with 5-OH and/or 7-OH groups show the higher cytotoxicity, and flavonoids with 3'-OMe and/or 5'-OMe groups plays positive but 6-OMe groups negative roles in the P-glycoprotein (Pgp) inhibition. It is believed that these SAR results can be taken into account for the development of flavonoids with high therapeutic index.